Chaplin's Essanay comedies. Vol. 1 [videorecording (DVD)] - Chaplin, Charlie, 1889-1977; Coleman, Frank J.; Turpin, Ben, 1874-1940; Purviance, Edna, 1896-1958; Mineau, Charlotte (Image Entertainment [distributor], 1999)
A collection of Chaplin's films at Essanay Studios. His new job: Charlie applies for a job as an actor at a film studio. A night out: Charlie and Turpin are drunks about town, starting at a cafe and ending in a risque hotel room mix-up with a pretty girl. The Champion: Pint-sized Charlie defeats the bone-crushing champion prizefighter with the able assistance of his bulldog. In the park: Charlie interferes in the lives of two star-crossed lovers. A Jitney elopement: Charlie rescues his sweetheart from an arranged marriage by posing as Count Chloride de Lime. featuring the Ford automobile.